Problemy migracji w Kodeksie Kanonów Kościołów Wschodnich - Orczykowski, Andrzej (Prawo Kanoniczne, 2007)
The Code of Canon Law of the Eastern Catholic Churches - as a basic statute book - took up the issues that arose due to the phenomenon of modern migration. However, the practical application of these basic statutes is left to the discretion of individual Eastern Churches. The Code contains not only a description of the phenomenon of migration and its problems; it also insists on official status for the faithful in their churches which are sui iuris. This can be seen in the individual canons in which the legislator tries to integrate the migrants while respecting and preserving their own rite. The Code of Canon Law of the Eastern Catholic Churches also places particular emphasis on the necessity to recognize m igrants’ pastoral needs and provides appropriate structures for them. It accurately defines the rules for migrants when they are living under the Church’s authority. The Code’s wholehearted support of pastoral work for migrants has been welcomed in Eastern Churches’ fundamental code of law. As a result it would seem that The Code of Canon Law of the Eastern Catholic Churches will play a big part in shaping the legal system of the particular Eastern Churches.